Da-Bu-Yin-Wan and Qian-Zheng-San Ameliorate Mitochondrial Dynamics in the Parkinson’s Disease Cell Model Induced by MPP+ - Gai, Cong; Feng, Wan-Di; Qiang, Tian-Yao; Ma, Hao-Jie; Chai, Yuan; Zhang, Shu-Jing; Guo, Zhen-Yu; Hu, Jing-Hong; Sun, Hong-Mei (Frontiers in Pharmacology, 2019)
To investigate the effect of Da-Bu-Yin-Wan and Qian-Zheng-San (DBYW and QZS) on mitochondrial mass in Parkinson’s disease (PD) cell model induced by 1-Methyl-4-phenylpyridinium Ion (MPP+). The SH-SY5Y cell was selected and treated with MPP+. The PD model was intervened with DBYW and QZS. CCK-8 method was used to detect the survival rate of cells in each group. Mitochondria was labeled by mitoTracker®Red CMXRos probe and observed by laser scanning confocal microscope, and ImageJ software was used to process images and measure mitochondrial form factors; Tetramethylrhodamine methyl ester was used to detect mitochondrial membrane potential (ΔΨm); Luciferase method was used to detect cellular ATP levels; Western-Blot technique was applied to detect the expression levels of Parkin protein, and the expression levels of Mfn1, Mfn2, OPA1, Drp1, and Fis1. We found that DBYW and QZS treatment significantly increased the cell survival rate, form factor (F-factor), mitochondrial activity and ΔΨm after MPP+ treatment, while the increase of ATP levels was not significant. In addition, the results of western blot analysis showed that the MPP+ induced increase in the expression of Drp1 and Fis1, as well as decrease in Parkin, Mfn1, Mfn2, and OPA1 were all partially revised by DBYW and QZS. In summary, our data strongly suggested that DBYW and QZS treatment can exert protective effects against PD related neuronal injury through regulation the homeostasis between mitochondrial fission and fusion.